Efeitos do treinamento de alta intensidade de corredores profissionais na saúde cardiovascular - Bittencourt, Celia Regina de Oliveira [UNIFESP] (2016)
Introduction: Physical activity has been universally recommended for cardiovascular disease prevention. However, the effects of intensive physical activity on cardiovascular protection are less reported. Objectives : To examine biochemical, nutritional, and ergo-respiratory parameters, and, particularly, to quantify the percentage of circulating endothelial progenitor cells (EPC) and amount of endothelial (EMP) and platelet (PMP) microparticles among professional runners. These parameters were compared with healthy non-athlete controls. Methods: Case control study includes professional runners and age and gender matched controls. Circulating EPC, EMP and PMP were quantified by flow-cytometry using specific antibodies. Lean and fat corporal mass were estimated by bioimpedance. Biochemical parameters were obtained fast after routine exercise in the day before. Results: Athletes had lower BMI, better metabolic and lipid profile (all p<0.05 vs. controls). Higher CEP (%) was observed in athletes (CD34/KDR+, p=0.038 vs. controls; CD133+/KDR+, p=0.018 vs. controls; but did not differ for CD34+/CD133+, p=0.51). Microparticles (EMP and PMP) were similar between athletes and controls. Athletes had higher mean (SE) VO2 peak group [59 (4) vs 48 (3) ml/kg.min, p<0.05). Conclusions: Intensive exercise is associated with increased circulating EPC without increase in microparticles. This favorable balance of vascular biomarkers is still associated with better anthropometric and biochemical parameters.